Integration and Interconnection of Human Concepts in Islamic and Transpersonal Psychology - Haryanto, Sri; Sila, Hendriyadi Bahtiar Daeng (International Journal of Islamic Educational Psychology, 2022)
This study describes the interconnection of human conceptions in Islamic and transpersonal psychology. The research method used was qualitative with a library research model and e-journal literature that discusses humans from Islamic and transpersonal psychology perspectives. The data collection technique was through documentation. The researchers documented the literature on human and psychological e-journals and then presented them systematically. The data analysis was carried out by data reduction, data presentation, and concluding. The researchers reduced human data and Islamic psychology accessed in e-journals, then systematically presented and analyzed them descriptively-interpretatively. The results revealed that the interconnection of human concepts in Islamic and transpersonal psychology was found in the following points; (1) examining humans in the three dimensions of somatic (body), psychic (mental), and noetic (spiritual); (2) the central theme of theoretical studies; and (3) spiritual awareness (transcendental).